PENDIDIKAN ISLAM DAN PENGEMBANGAN AKHLAK: DIALEKTIKA KONSEP, NILAI, DAN RELEVANSI KONTEMPORER - Maya Pitri Ayu Ningsih; Nur Elida Siregar (Yayasan Baitul Hikmah al-Zain, 2025)
Islamic education plays a very important role in developing moral values ​​in individuals, especially in the formation of good character and behavior. Morals in the Islamic perspective are not only limited to morality, but also include manners in relationships with Allah, fellow human beings, and the universe. Islamic education, both formal and informal, serves as a means to instill these values, leading to an integrated improvement in self-quality between spiritual, social, and emotional aspects. Through learning the Qur'an, hadith, and various other Islamic studies, students are taught to develop noble morals, such as honesty, patience, humility, and caring for others. Islamic education also encourages the application of these values ​​in everyday life, both at home, school, and in society. Teachers as agents of change are expected to be role models for students in practicing good morals. In this perspective, Islamic education not only aims to create individuals who are intellectually intelligent, but also emotionally and socially intelligent. Through a continuous educational process, moral values ​​can be continuously nurtured and applied, thus creating a more harmonious, loving, and responsible society. Thus, Islamic education plays a very vital role in shaping the character of a nation with noble character.